2016
DOI: 10.4269/ajtmh.15-0895
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Low Community Sanitation Coverage Using Environmental and Sociodemographic Factors in Amhara Region, Ethiopia

Abstract: Abstract. This study developed and validated a model for predicting the probability that communities in Amhara Region, Ethiopia, have low sanitation coverage, based on environmental and sociodemographic conditions. Community sanitation coverage was measured between 2011 and 2014 through trachoma control program evaluation surveys. Information on environmental and sociodemographic conditions was obtained from available data sources and linked with community data using a geographic information system. Logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This is consistent with the finding in Hulet Eju Enessie district, Ethiopia that households in highland climatic zone were more likely to own latrines compared to their counterpart lowlanders [5]. This might be related to variations specifically in the soil and/or temperature in the climatic zones which are believed to affect the construction and durability of latrines [1719]. Households whose kebeles were subjected to CLTS program were 1.78 times more likely to have latrines compared to those that did not part of the CLTS program.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the finding in Hulet Eju Enessie district, Ethiopia that households in highland climatic zone were more likely to own latrines compared to their counterpart lowlanders [5]. This might be related to variations specifically in the soil and/or temperature in the climatic zones which are believed to affect the construction and durability of latrines [1719]. Households whose kebeles were subjected to CLTS program were 1.78 times more likely to have latrines compared to those that did not part of the CLTS program.…”
Section: Discussionsupporting
confidence: 88%
“…However, slightly lower evidence was reported from Hullet Ejj Enese of the Amhara region of Northern Ethiopia (92%) and Nepal (94.3%) [ 17 , 29 ]. The discrepancy among the study findings might be related to climatic zones which are believed to affect the construction and durability of latrines for sustainable use [ 30 32 ]. Progressive sanitation facilities and good community awareness might be the reason in Nepal [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many of the prior studies conducted in Ethiopia and other African nations having a larger family, an advanced education, and being male were associated with the increased adoption and utilization of latrines [16][17][18][19]. Also, Qualitative studies on sanitation have identified the un-affordability of building materials [20] and the lack of awareness of the health risks associated with open defecation as a hindrance to the adoption of sanitation facilities [21].…”
Section: Fundingmentioning
confidence: 99%